PEMAHAMAN PELAKU UKM TAHU SUMEDANG TERHADAP HAK DAN KEWAJIBAN PAJAK PENGHASILAN FINAL DALAM MEMENUHI KEPATUHAN PERPAJAKAN - Rachel Evelyn Cahyadi (Business Administration Department - Universitas Katolik Parahyangan, 2022)
Determination of government regulation number 46 of 2013 on the final income tax for SMEs aims to facilitate taxpayers in calculating the amount of tax to be paid, but the determination of government regulation number 46 of 2013 has not run smoothly, there is still noncompliance indicated by the taxpayer for that regulation, especially among SMEs. This study aims to determine the level of understanding of the rights and obligations of SMEs and final income tax liability in meeting tax compliance. The type of research used in this study is exploratory. Data were collected by conducting interviews and distributing questionnaires to 52 SMEs. The analysis technique used by writer in this research is descriptive analysis.The results of this study show that there is a lack of insight into the rights of SME as a taxpayer. However, SME taxpayers quite understand their obligations a taxpayer and they quite comply with the tax regulations.